Comparing Trunk and Lower Extremity Kinematic Variables during Side-Cutting Maneuver in Healthy and Anterior Cruciate Ligament Reconstructed Athletes - Mohammad Aziminia; Ali Abbasi (Islamic Azad University, Hamedan Branch, 2022)
Objective:  However, due to the long-term recovery process in anterior cruciate ligament injury and the occurrence of secondary problems after surgery, as well as the lack of adherence to postoperative rehabilitation programs, however, there is a risk of re-rupture of this ligament. Therefore, the aim of the present study was to compare the kinematic parameters of the trunk and lower limbs during shear maneuvers in healthy and reconstructed athletes of the anterior cruciate ligament. Methods: The subjects of this study included 34 male athletes who were randomly divided into experimental (reconstructed cruciate ligament) and control (healthy) groups. Kinematic and Kinetic data were recorded using a camera motion capture system (Vicon, Oxford Metrics Ltd) sampling at 200 Hz, synchronously with ground reaction forces from force platform at 1000 Hz (Kistler AG, Winterthur, Switzerland). The calculation of kinematic variables from initial foot contact to toe-off with force plate was performed by Visual3D (C-Motion Inc) software. Results: The results of independent t-test concerning trunk flexion, hip and ankle flexion did not show a significant difference between the healthy and ACLR groups (P>0.05), but decrease in knee joint flexion in the ACLR group,was significant (P=0.008) compared to the healthy group Also in the ACLR group, an increase in knee joint valgus was significant (P=0.05). ACLR group's tibia rotation with respect to femur was also significant (P=0.038) compared to that of the healthy group. Conclusion: Due to the change in the kinematics of ACLR group compared to that of the healthy individuals and the increased risk of re-rupture in ACLR individuals, it is suggested that in designing exercises and postoperative rehabilitation courses, proper training of techniques and movements be performed to reduce the likelihood of re-injury by achieving the desired kinematics in the joints and limbs as well as the athletes' awareness.